ChemInform Abstract: 3‐Methyl‐4‐oxa‐5‐azahomoadamantane as an Organocatalyst for the Aerobic Oxidation of Primary Amines to Oximes in Water. Issue 33 (August 2015) - Yu, Jiatao; Jin, Yong; Lu, Ming
Abstract This green and selective oxidation of amines gives E‐type oximes in high yields.